1974
DOI: 10.1111/j.1365-2672.1974.tb00418.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Chloride as a Cause of Low Numbers of Rhizobium in Legume Inoculants

Abstract: Summary. A rapid reduction, after manufacture, in numbers of Rhizobium trifolii in commercial legume inoculants was observed in 1971 and explained by the presence of high concentrations of sodium chloride in the peat used as carrier material. A strain of R. trifolii growing in broth proved to be more sensitive to sodium ions than did 2 strains of R. meliloti but was more tolerant of up to 0.3% of chloride. The effect of salt differed somewhat according to the source of peat used as carrier, but peat containin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1979
1979
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 5 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…Decreased photosynthesis in response to salt stress might be expected to decrease carbohydrate flow to the root system and root exudation, thereby limiting the establishment of symbiotic plant/microbe interactions in the rhizosphere. Although it is well known that high salinity can decrease nodulation of legumes by rhizobia (Steinborn and Roughley 1974;Steil et al 2003;Barea et al 2005), effects of salinity on associative PGPR inhabiting the rhizosphere may be variable. Although high salinity increased root colonisation of lettuce with PGPR Pseudomonas mendocina (Steil et al 2003), pea root colonisation of V. paradoxus 5C-2 was independent of salinity level (Table 1), similar to experiments where soil drying had no effect on, or even increased, colonisation of V. paradoxus 5C-2 (Belimov et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Decreased photosynthesis in response to salt stress might be expected to decrease carbohydrate flow to the root system and root exudation, thereby limiting the establishment of symbiotic plant/microbe interactions in the rhizosphere. Although it is well known that high salinity can decrease nodulation of legumes by rhizobia (Steinborn and Roughley 1974;Steil et al 2003;Barea et al 2005), effects of salinity on associative PGPR inhabiting the rhizosphere may be variable. Although high salinity increased root colonisation of lettuce with PGPR Pseudomonas mendocina (Steil et al 2003), pea root colonisation of V. paradoxus 5C-2 was independent of salinity level (Table 1), similar to experiments where soil drying had no effect on, or even increased, colonisation of V. paradoxus 5C-2 (Belimov et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The detrimental effects of salt stress on nodulation, plant growth and nitrogen fixation have been reported for many legumes including alfalfa, peas, mung beans and cowpeas (Balasubraminiam & Sinha, 1976;Upchurch & Elkan, 1977;Wilson & Norris, 1970: Yadav & Vyvar, 1971. The presence of high sodium chloride has been reported to reduce the number of rhizobia in legume inoculants (Steinborn & Roughly, 1974, 1975. Tolerance to salt stress may be an important part of saprophytic competence and competitiveness in rhizobia.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, commercial strains of Rhizobium usually cannot tolerate or function under high levels of osmotic stress caused by salinity or drought, e.g., salt in peat used as a carrier reduced the viability of R. trifolii in legume inoculants produced in Australia (Steinborn and Roughley, 1974). Wilson and Norris (1970) reported that commercial R. mad and Campbell 1985;, it is considerably higher than the 0.5 to 0.7% range reported by Yadav and Vyas (1971a, b).…”
Section: Introductionmentioning
confidence: 99%